How does marriage affect the wages of men in Australia? - Birch, E.; Miller, Paul (Wiley-Blackwell Publishing Asia, 2006)
This paper investigates how marriage affects the wages of men in Australia. It finds that there are wage advantages associated with marriage, although men benefit most, in terms of wages, from being married to a more highly educated woman. This advantage is greater where the wife does not work. These findings are more aligned with human capital theory than with assortative mating theory. The focus on the family reflects many of Bob Gregory's contributions, including his study in the Journal of Labor Economics in 2005 (Meng & Gregory 2005).